Efisiensi Relatif UKM Sarung Goyor Menggunakan Integrasi Fuzzy dan Data Envelopment Analysis (DEA) - Ida Giyanti; Anita Indrasari (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2018)
Sarong goyor becomes one of the excellent product of Sukoharjo city. Most of the production centers of small medium enterprise (SME) sarongs have been exported overseas, especially to African countries and the Middle East. The business of making this sarong is a hereditary business that is still maintained until now, which in the production process is still done manually using non-machine loom (ATBM). This study aims to determine the relative efficiency of SMEs gloves by using the integration of fuzzy concepts and Data Envelopment Analysis (DEA). The input variables considered include raw material costs (CMTR), direct labor costs (CDHR), and other costs (FCST). The output variables analyzed consist of sales (REVN) and profit (PRFT). The results show that there are four SMEs as an inefficient Decision Making Unit (DMU), in one DMU operating on decreasing return to scale (DRS) and three DMUs operating on increasing return to scale (IRS).